Improving the residual risk of renal and cardiovascular outcomes in diabetic kidney disease: A review of pathophysiology, mechanisms, and evidence from recent trials. Issue 3 (1st December 2021) - Chaudhuri, Ajay; Ghanim, Husam; Arora, Pradeep
Abstract: Based on global estimates, almost 10% of adults have diabetes, of whom 40% are estimated to also have chronic kidney disease (CKD). Almost 2 decades ago, treatments targeting the renin‐angiotensin system (RAS) were shown to slow the progression of kidney disease. More recently, studies have reported the additive benefits of antihyperglycaemic sodium‐glucose co‐transporter‐2 inhibitors in combination with RAS inhibitors on both CKD progression and cardiovascular outcomes. However, these recent data also showed that patients continue to progress to kidney failure or die from kidney‐ or cardiovascular‐related causes. Therefore, new agents are needed to address this continuing risk. Overactivation of the mineralocorticoid (MR) receptor contributes to kidney inflammation and fibrosis, suggesting that it is an appropriate treatment target in patients with diabetes and CKD. Novel, selective non‐steroidal MR antagonists are being studied in these patients, and the results of two large recently completed clinical trials have shown that one such treatment, finerenone, significantly reduces CKD progression and cardiovascular events compared with standard of care. This review summarizes the pathogenic mechanisms of CKD in type 2 diabetes and examines the potential benefit of novel disease‐modifying agents that target inflammatory and fibrotic factors in these patients.